2016
DOI: 10.1371/journal.pone.0166451
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Treatment Uptake among Patients Who Have Received Opioid Substitution Treatment: A Population-Based Study

Abstract: Background and AimsThere is limited data on hepatitis C (HCV) treatment uptake among people who inject drugs including individuals receiving opioid substitution treatment (OST). We aimed to calculate cumulative HCV treatment uptake, estimate annual treatment rates, and identify factors associated with HCV treatment among individuals who have received OST in Norway.MethodsThis observational study was based on linked data from The Norwegian Prescription Database and The Norwegian Surveillance System for Communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 42 publications
1
33
0
1
Order By: Relevance
“…In most high-income countries, PWID accounted for the majority of people with chronic hepatitis C and new infections [3,4]. As well as the need for an expansion of opioid substitution therapy and accompanying preventive efforts such as education, counselling and needle exchange programmes [27], HCV treatment uptake in this patient group needs to be enhanced [28] to reduce disease burden world-wide. To overcome the reluctance of treating HCV infection in drug users, more data on therapy in this patient group, such as response rates and safety features, might be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…In most high-income countries, PWID accounted for the majority of people with chronic hepatitis C and new infections [3,4]. As well as the need for an expansion of opioid substitution therapy and accompanying preventive efforts such as education, counselling and needle exchange programmes [27], HCV treatment uptake in this patient group needs to be enhanced [28] to reduce disease burden world-wide. To overcome the reluctance of treating HCV infection in drug users, more data on therapy in this patient group, such as response rates and safety features, might be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…dropout from OAT would precipitate dropout from DAA). OAT retention is a strong predictor of long-term ART adherence among PWID (Roux et al, 2009), is associated with HCV treatment initiation (Midgard, Bramness, Skurtveit, Haukeland, & Dalgard, 2016), and has been found to improve adherence in studies conducted during the pegylatedinterferon era (Dimova, Zeremski, Jacobson, Hagan, & Des Jarlais, 2013). However, studies of people on OAT and recent injectors have found both populations able to complete a twelve week DAA treatment regimen irrespective of ongoing injecting drug use or OAT (Mason et al, 2017; Morris et al, 2017; Read et al, 2017), and studies which randomized people to immediate or delayed DAA treatment within OAT settings have observed loss to follow-up in the delayed treatment arms (Dore et al, 2016; Hilsden, Macphail, Grebely, Conway, & Lee, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, <10% of hepatitis C patients have received treatment in most European countries . In recent years, there has been a slight increase, including Norway, although recent estimates indicate that only about 10% of Norwegian patients with hepatitis C had been cured before the introduction of sofosbuvir in 2014 . The proportion of infected people on treatment stands in sharp contrast to the WHO goals of reducing the incidence of hepatitis C by 90% and mortality by 65% by 2030 (http://apps.who.int/iris/bitstream/10665/246177/1/WHO-HIV-2016.06-eng.pdf?ua=1).…”
Section: Introductionmentioning
confidence: 99%